PEDAGOGICAL FOUNDATIONS OF EDUCATING YOUNG PEOPLE IN THE SPIRIT OF SPIRITUAL MATURITY - N. Ahmadova; M.A. Khamidova (Scholar Express Journals, 2023)
The article is specific to today's globalization process, which describes in detail the essence and significance of the education of young people in the spirit of spiritual development. The article sets out in detail national traditions, Traditions and values in the education of love and devotion to the motherland and humanistic values in the homeland.
Keywords: ideal person; scientist; thinker; national idea